Aloe-emodin plus TIENAM ameliorate cecal ligation and puncture-induced sepsis in mice by attenuating inflammation and modulating microbiota - Su, Jingqian; Deng, Xiaohui; Hu, Shan; Lin, Xinrui; Xie, Lian; Ye, Hui; Lin, Congfan; Zhou, Fen; Wu, Shun; Zheng, Liling (Frontiers in Microbiology, 2024)
Despite the high sepsis-associated mortality, effective and specific treatments remain limited. Using conventional antibiotics as TIENAM (imipenem and cilastatin sodium for injection, TIE) is challenging due to increasing bacterial resistance, diminishing their efficacy and leading to adverse effects. We previously found that aloe-emodin (AE) exerts therapeutic effects on sepsis by reducing systemic inflammation and regulating the gut microbiota. Here, we investigated whether administering AE and TIE post-sepsis onset, using a cecal ligation and puncture (CLP)-induced sepsis model, extends survival and improves physiological functions. Survival rates, inflammatory cytokines, tissue damage, immune cell populations, ascitic fluid microbiota, and key signaling pathways were assessed. Combining AE and TIE significantly enhanced survival rates, and reduced inflammation and bacterial load in septic mice, indicating potent antimicrobial properties. Moreover, substantial improvements in survival rates of AE + TIE-treated mice (10% to 60%) within 168 h were observed relative to the CLP group. This combination therapy also effectively modulated inflammatory marker (interleukin [IL]-6, IL-1β, and tumor necrosis factor [TNF]-α) levels and immune cell counts by decreasing those of B, NK, and TNFR2+ Treg cells, while increasing that of CD8+ T cells; alleviated tissue damage; reduced bacterial load in the peritoneal cavity; and suppressed the NF-κB signaling pathway. We also observed a significantly altered peritoneal cavity microbiota composition post-treatment, characterized by reduced pathogenic bacteria (Bacteroides) abundance. Our findings underscore the potential of AE + TIE in treating sepsis, and encourage further research and possible clinical implementations to surmount the limitations of TIE and amplify the therapeutic potential of AE.